Hotel-daddy-wasp-machine. Issue 9 (2nd September 2022) - Collignon, Fabienne
ABSTRACT: In this article on The Shining, I investigate a becoming-insect that occurs with respect to Jack Torrance as a result of his enmeshing with the being of the Hotel, configured as wasp-force in both novel and film. I deviate from Deleuze and Guattari's understanding of becoming in order to think through how becoming, or swarming (used interchangeably), comes to function as masculine politics of control. The first part of the essay maps the processes of becoming onto The Shining, and proceeds to investigate the phenomenon of fascination, relying on Roger Caillois' work on mimetic insects, in part two. The final part focuses on the insectile sound-image of the Hotel, above all using Michel Chion's writings. My intention is to use The Shining in order to think through and interrupt the automatic understanding of becoming-insect/swarming as operating beyond the sovereignty of the father and to reflect on The Shining 's continued parasitic apparitions in contemporary culture and politics.